Multisensoriality at the Alhambra: Tours for Blind and Partially Sighted People to the Bab Al-Saria Temporary Art Exhibition - Soler Gallego, Silvia; Luque Colmenero, María Olalla (Eikón / Imago, 2019)
The aim of this article is to provide a detailed description of an applied research project in museum audio description. Specifically, it proposes a method for conducting multisensory guided tours for blind and partially sighted (BPS) people to art museums and exhibitions. This article offers samples of the audio descriptions and verbal instructions for tactile exploration of relief images and three-dimensional replicas used in tours for BPS people to the Bab Al-Sariatemporary art exhibition at the Alhambra, Granada.